PENGARUH PERSEPSI DIMENSI KUALITAS LAYANAN TERHADAP NIAT PEMBELIAN ULANG (Studi Kasus pada Swalayan IT Mart UNITA) - Eldon, Mokhamad; Desi Rahmawati (BEMJ : Business, Entrepreneurship, and Management Journal, 2023)
This study aims to explain the effect of the variable perceived service quality on repurchase intentions which is moderated by the variable student satisfaction at the IT Mart Supermarket at Tulungagung University. The sample in this study were some students who shopped at the IT Mart supermarket at Tulungagung University, the number was 100 students and the sampling technique used was purposive sampling technique. Data obtained through primary data by distributing questionnaires. Analysis was performed using multilevel regression analysis. The results showed that the perceived service quality variable had an effect on repurchase intentions. Perceived service quality variable and satisfaction variable together influence repurchase intention. The perceived service quality variable influences repurchase intention through satisfaction as a moderating variable for IT Mart supermarkets at Tulungagung University. The implications for IT Mart supermarket managers at Tulungagung University can develop marketing strategies to improve the quality of service to their consumers.